Preparation of robust synthetic control samples and their use in a metatranscriptomic clinical test - Ryan Toma; Lan Hu; Guru Banavar; Momchilo Vuyisich (Scientific Reports)
Abstract Metatranscriptomics (MT) has the potential to revolutionize the field of molecular diagnostics. Due to the complexity of MT diagnostic models, positive and negative control materials for specific disease indications can be difficult to obtain. Controls must often be sourced directly from patients. This introduces logistical burdens, assay variability, and limits high throughput clinical laboratory operations. To overcome this limitation, we developed a method for generating Synthetic Control (SC) samples, which duplicate the nucleic acid signature of complex clinical specimens and produce the desired test outcome. SCs can be easily and cost-effectively produced in large quantities (> 100,000 SCs per amplification cycle), enabling high throughput diagnostic testing. Here, we report the generation of Synthetic Positive Control (SPC) samples. SPCs were validated and implemented in a clinical laboratory. The SPCs produced robust positive signals (average OC risk score of 0.996) and high levels of reproducibility (%CV of 0.29%) in a high throughput automated CLIA laboratory. SCs are a novel and useful method for the generation of high quality controls for MT-based diagnostic tests, and their adoption could herald the widespread use of MT tests in molecular diagnostics.